ACT-Informed Treatment of Co-morbid Psychiatric Disorders in the Postpartum Period: A Case Report. (February 2023) - Grove, Lindsey; Roche, Anne I.; Doyle, Rena; Stowe, Zachary N.; Thomas, Emily B. K.
The literature describing psychological interventions for co-occurring obsessive-compulsive disorder (OCD) and post-traumatic stress disorder (PTSD) is limited. Acceptance and Commitment Therapy (ACT) is a transdiagnostic intervention that targets functionally avoidant behavior underlying both OCD and PTSD. The current case report describes how an ACT-informed approach to treatment was implemented over 14 sessions to treat co-occurring OCD and PTSD in a 9-months postpartum adult woman. The patient was initially referred to psychotherapy by her psychiatrist and showed high motivation to engage in treatment. This case presentation outlines how the intervention targeted core ACT processes while also incorporating components from both exposure and response prevention (ERP) and cognitive processing therapy (CPT) to address the patient's presenting concerns. Measurements of OCD and PTSD symptom severity, as well as of depressive and anxiety symptoms, over the course of treatment are included. Health-related comorbidities, psychiatric medications, and implications are discussed.